Peningkatan Keahlian Pembukuan Usaha Bagi UMKM Pulau Pramuka Jakarta - Lailah Fujianti; Basis Gumilarsih; Susilawati Susilawati; Indah Masri; Amelia Oktrivina (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
Small and Medium Enterprises (MSMEs) often need help maintaining proper bookkeeping practices. This crucial aspect can help them understand their financial health, keep track of their performance, and make informed decisions. However, many MSME owners need more bookkeeping skills or time to manage it effectively. As a result, they may need to realize the importance of keeping accurate records. The issue is particularly acute amongst MSMEs in Pulau Pramuka, where low levels of education contribute to the problem. To tackle this issue, a dedicated training and bookkeeping assistance service has been established to support MSME actors on the island. This initiative aims to enable MSMEs to maintain proper bookkeeping practices and make informed business decisions, which can improve their financial performance and long-term sustainability.